Production and optimization of antibacterial metabolites from endophytic fungi Nigrospora sp. ML#3 - Kamini Sandey, Ravindra Prasad Aharwal, Suneel Kumar, Sardul Singh Sandhu (Journal of Applied Pharmaceutical Science, 2015)
Ailanthus excelsa Roxb. is one of the most important plant which has a specific place in Ayurveda and phytotherapy. The tribal people generally used this plant for anthelminthic, anti-fertility, rejuvenation and anti-malarial against Plasmodium falciparum. In the present study total four endophytic fungi were isolated from the leaves of medicinal plant A. excelsa for the production of antibacterial bioactive compounds against five pathogenic bacterial strains. Various cultural conditions like media, pH, temperature and quarantine period was also optimized for the maximum production of antibacterial bioactive compounds from the potent fungus. After each optimizing step, the extracts were tested for antibacterial activity by agar well diffusion method and the best condition was selected for further process.
Keywords: Endophytic fungi, Bioactive compound, Optimization, Antibacterial activity.